2011
DOI: 10.1007/s10047-011-0563-y
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of paravalvular leakage as a complication occurring in the late phase after surgery

Abstract: Paravalvular leakage (PVL) remains an unavoidable late complication after valve surgery. We indicate surgery only cases with progressive congestive heart failure and/or hemolytic anemia. We review our clinical experiences of PVL surgery. Between 1992 and 2009 we experienced 8 cases of aortic PVL-6 subjects after primary aortic valve replacement (AVR) and 2 subjects after re-AVR-and 10 subjects with mitral PVL-5 cases after primary mitral valve replacement (MVR) and 5 cases after re-MVR. Mitral PVL began in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Conversely, mitral PVL was mainly caused by cutting annulus tissue around the anterior commisurae after primary MVR, and by a valve-on-valve structure on the middle scallop of the posterior leaflet or circumferentially after re-MVR. They concluded that valve-on-valve replacement, which was a major cause of PVL after re-MVR, should be avoided in a re-MVR procedure, and that cautious follow-up is necessary, even in the late phase after surgery, especially for patients who have undergone MVR [32].…”
Section: Artificial Valvementioning
confidence: 97%
“…Conversely, mitral PVL was mainly caused by cutting annulus tissue around the anterior commisurae after primary MVR, and by a valve-on-valve structure on the middle scallop of the posterior leaflet or circumferentially after re-MVR. They concluded that valve-on-valve replacement, which was a major cause of PVL after re-MVR, should be avoided in a re-MVR procedure, and that cautious follow-up is necessary, even in the late phase after surgery, especially for patients who have undergone MVR [32].…”
Section: Artificial Valvementioning
confidence: 97%
“…Most are asymptomatic and benign, but some may cause symptoms due to heart failure, arrhythmia, endocarditis or hemolysis. Although surgical procedures have been well established, and recent technological advances have led to more hemodynamically efficient prosthetic heart valves, PVL is still an unavoidable complication of prosthetic valve implantation [1,2]. PVLs occur with an incidence of 2-10% in the aortic position and 7-17% in the mitral position [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Çoğunlukla asemptomatik ve zararsız olmakla birlikte, bazen kalp yetmezliği, aritmi, endokardit ve hemolize sebep olarak semptomlara yol açabilmektedir. Cerrahi yöntemlerin iyileşmesine ve teknolojik gelişmeler ile birlikte hemodinamik açıdan daha verimli protez kalp kapaklarının geliştirilmiş olmasına rağmen PVK gelişimi halen protez kapak cerrahisinin olası komplikasyonları arasındadır 1,2 . PVK insidansı aortik kapak replasmanı sonrası %2-10, mitral kapak replasmanı sonrası %7-17 arasında bildirilmiştir 3,4 .…”
unclassified